How to design wastewater systems for local conditions in developing countries - Robbins, David M.; Ligon, Grant C. (IWA Publishing, 2014)
Designing Wastewater Systems According to Local Conditions is a practical handbook providing a step-by-step approach to the techniques used for characterizing wastewater sources and investigating sites where collection, treatment and reuse/disposal technologies will be installed.